Pluralism, religious bias and pathologizing: The interpretation and use of D. W. Winnicott's theories in the psychoanalytic study of religion. - Berg, Daniel F. (University of Ottawa (Canada), 1998)
This thesis is a close analysis of the work of five scholars in psychology of religion, scholars who have incorporated elements of D. W. Winnicott's psychoanalytic object relations theories into their own work. In this group of five there are three who pioneered the use of Winnicott in psychology of religion and two whose work is more recent. The point of my research is to demonstrate how religious bias affects the interpretation and use of Winnicott by scholars of religion, or more positively, to assess to what degree these scholars can appreciate the experiences of those whose values and religiosity differ from their own. I demonstrate that the religious psychologists who pioneered the use of Winnicott tend to pathologize those experiences and groups that diverge from their own ideals and I argue that this tendency contaminates their interpretation of his theories. Fortunately I have not found this tendency in the work of the other two more contemporary psychologists of religion. The political use of pathologizing is not new to analytic circles. Analysts of the psychoanalytic movement show how readily proponents of a new stream of interpretation or the establishment that resists the new approaches get pathologized: reformers are pathologized by the mainstream and vice versa. What I am seeking is an approach to helping that does not pathologize because of religious differences, but rather seeks to release the healing potential within the individual and his or her own system of belief. I am not the first to diagnose religious bias in the work of psychology of religion scholars. In response to the prevalence of what he calls "religious psychologists" in psychology of religion, and the corresponding problems of religious bias, Benjamin Beit-Hallahmi has pioneered the use of the label "ethnocentric," an anthropological term arising from the evaluation of anthropologists' work with people from other cultures, as a word to describe how religious bias affects scholarly activity in psychology of religion. Beit-Hallahmi like others who have identified this type of problem recommends that biographical factors and the scholar's religious affiliation and definition of religion be used as analytical tools for better comprehending a psychologist of religion's theories. In keeping with this recommendation and perhaps new trend in psychology of religion, I, as a means to better contextualize these five scholars' use of Winnicott, pay close attention to the biographical material that can be obtained for each of them as well of course as for Winnicott himself. In my interpretation of Winnicott, I find his approach to be the antithesis of ethnocentric, religiously biased pathologizing, both in his life experiences when he himself was subject to this kind of political analytical denigration, as well as in his clinical and theoretical approaches. I find Winnicott to be a pluralist, one who believed that the cultural creations of humankind are infinitely varied and not subject to classification. Unfortunately, several psychoanalytic scholars of religion have introduced pathological distinctions into Winnicott's interpretations of the human condition, and it is the work of this thesis to carefully analyse these innovations situating them in their religious contexts. Fortunately, there are also more pluralistic and less ethnocentric uses of Winnicott's theory, and building on these and my own analysis of Winnicott I conclude with suggestions for a more humane and enriching psychoanalysis of religion. (Abstract shortened by UMI.)
Keywords: Religion, General.